The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1152/ajpregu.1988.254.1.r17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of continuous infusions of CCK-8 on food intake and body and pancreatic weights in rats

Abstract: The ability of cholecystokinin (CCK) to act as a long-term satiety factor was assessed by its continuous infusion into the jugular veins of rats. Animals receiving a low dose of cholecystokinin octapeptide (CCK-8) (0.6 microgram CCK-8.kg body wt-1.h-1) did not show any significant differences in body weight changes or in food consumption from rats receiving saline and a group of unoperated controls over the 7-day infusion period. A 19.3-fold greater dose of CCK-8 (11.6 micrograms.kg body wt-1.h-1) did cause a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…Continuous administration of other anorexigenic peptides (cholecystokinin, amylin, GLP-1) by osmotic minipump has also been reported to produce either no effect or a transient reduction in daily food intake in rodents (2,4,11,12,25). One possible explanation for these transient responses is that early peptide-induced reductions in daily food intake and adiposity elicit a delayed compensatory response to restore energy balance mediated by a reduction in leptin signaling to the brain (2,17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuous administration of other anorexigenic peptides (cholecystokinin, amylin, GLP-1) by osmotic minipump has also been reported to produce either no effect or a transient reduction in daily food intake in rodents (2,4,11,12,25). One possible explanation for these transient responses is that early peptide-induced reductions in daily food intake and adiposity elicit a delayed compensatory response to restore energy balance mediated by a reduction in leptin signaling to the brain (2,17).…”
Section: Discussionmentioning
confidence: 99%
“…4). During the subsequent 10-day treatment period, 1-h IV infusions of PYY(3-36) at 30 pmol⅐kg Ϫ1 ⅐min Ϫ1 significantly reduced food intake on successive days by 31,20,24,21,25,17,19,16,15 and 23%, respectively, compared with the vehicle-treated group (Figs. 4 and 5).…”
Section: Effects Of 1-h IV Infusions Of Pyy(3-36) Every Other Hour Onmentioning
confidence: 95%
“…Several studies have since shown that continuous systemic administration of PYY(3-36) by osmotic minipump can reduce food intake and body weight in rodents but only transiently (3,36,41,42,44). Other known anorexigenic substances (amylin, glucagon-like peptide-1 receptor agonists, cholecystokinin, melanocortin receptor agonists) have also been reported to produce only transient effects on daily food intake and body weight in rodents when administered continuously by osmotic minipump (3,9,18,20,30,31,35,36,38,41,42,44). Reasons for these inconclusive results include development of a compensatory increase in food intake between bolus injections, tolerance to continuous or frequent administration of the substances, and redundancy and plasticity in the energy regulatory system.…”
mentioning
confidence: 99%
“…Continuous osmotic minipump administration of many known anorexigenic substances [PYY , amylin, glucagon-like peptide-1 receptor agonists, cholecystokinin, melanocortin receptor agonists] has been reported to produce transient reductions in daily food intake in rodents (3,9,18,20,30,31,35,36,38,41,42,44). One possible explanation for these transient responses is that early substance-induced reductions in daily food intake and adiposity elicit a delayed compensatory response to restore energy balance mediated by a reduction in leptin signaling to the brain (5,22).…”
mentioning
confidence: 99%
“…The first gut hormone shown to inhibit food intake after exogenous infusion in rodents was CCK (cholecystokinin). Peripheral CCK has a brief but fastacting effect, decreasing food intake, and thus is thought to play a role in satiety and meal termination [41].…”
Section: Gastrointestinal Peptidesmentioning
confidence: 99%